Theoretical investigations on the tip-functionalised carbon nanotubes interacting with water. (12th September 2008) - Wongchoosuk, Chatchawal; Krongsuk, Sriprajak; Kerdcharoen, Teerakiat
Interactions between single-walled carbon nanotubes (SWNTs) and water molecules were studied using first principle calculations and molecular dynamics simulations. The SWNTs were modelled by varying the diameter ranging from the chiral vector (6, 0) to (9, 0) and by modifying the tube ends terminated with hydroxyl (&ndashOH) and carboxyl (&ndashCOOH) functional groups. Water and SWNT molecules were modelled using the SPC model and a flexible model based on the OPLS force field respectively. The first principle NBO charges were used for describing the tube-water electrostatic interactions. The results indicate that the movement of water into the COOH-SWNT is rather different from the pristine and OH-functionalised nanotubes. Water molecules prefer to localise around the SWNTs' tips than other parts. Hydrophilic behaviour of functionalised SWNT is improved over the pristine tube in agreement with experiments. The COOH-SWNT also shows the confinement of water molecules that may be useful for H2O transport.